When Singing Is Deadly: Improvising a New Reality for Music Therapists - Oddy, Nicola; Worden, Rebecca (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Nicola Oddy and Rebecca Worden discuss music therapy and the pandemic in this contribution to the special issue.